UPAYA TEORITIS PENANGGULANGAN KENAKALAN ANAK (JUVENILE DELIQUENCY) - Syahrul Akmal Latief; Muhammad Zulherawan (SISI LAIN REALITA, 2020)
Current technological developments have had a lot of bad effects on children, causing child delinquency and lately we often hear news about children, both children as victims and as perpetrators of delinquency. To solve the problem of children's delinquency must be done and based on a comprehensive understanding of the causes. So this article aims to discuss the causes of child delinquency from both the theoretical and conceptual perspectives as well as the scope of law and methods for dealing with child delinquency in Indonesia. The problem of juvenile delinquency continues to increase based on data from the KPAI of the Republic of Indonesia showing that there were 11,492 cases of delinquency and violating the law in 2019 so that several approaches are needed to prevent and overcome current juvenile delinquency which is mostly done through a repressive approach so that appropriate methods and approaches to address juvenile delinquency problems must be carried out based on a deep understanding of the causes of juvenile delinquency.